2011
DOI: 10.1029/2011gl048501
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting calcification responses to ocean acidification between two reef foraminifers harboring different algal symbionts

Abstract: Ocean acidification, which like global warming is an outcome of anthropogenic CO2 emissions, severely impacts marine calcifying organisms, especially those living in coral reef ecosystems. However, knowledge about the responses of reef calcifiers to ocean acidification is quite limited, although coral responses are known to be generally negative. In a culture experiment with two algal symbiont‐bearing, reef‐dwelling foraminifers, Amphisorus kudakajimensis and Calcarina gaudichaudii, in seawater under five diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 29 publications
(34 reference statements)
3
39
0
Order By: Relevance
“…One species with a porcelaneous shell decreased in size with increasing pCO 2 . Species-specific responses have been confirmed in a study by Hikami et al (2011). Studies of Foraminifera from natural CO 2 seeps with locally decreased pH reported increasing incidences of altered shell structure, decreasing population densities, declining diversity in calcifying Foraminifera, and increasing proportion of Foraminifera with agglutinated shells towards low pH/high pCO 2 (Dias et al 2010;Fabricius et al 2011;Uthicke and Fabricius 2012;Uthicke et al 2013).…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…One species with a porcelaneous shell decreased in size with increasing pCO 2 . Species-specific responses have been confirmed in a study by Hikami et al (2011). Studies of Foraminifera from natural CO 2 seeps with locally decreased pH reported increasing incidences of altered shell structure, decreasing population densities, declining diversity in calcifying Foraminifera, and increasing proportion of Foraminifera with agglutinated shells towards low pH/high pCO 2 (Dias et al 2010;Fabricius et al 2011;Uthicke and Fabricius 2012;Uthicke et al 2013).…”
Section: Introductionsupporting
confidence: 50%
“…A small but not significant increase in growth was observed in M. vertebralis in the treatment exposed to elevated pCO 2 (738 latm) at 28°C. A slight growth enhancement was observed in other porcelaneous species (Vogel and Uthicke 2012), whereas other studies reported reduced growth at medium to high pCO 2 levels (700-1,100 latm) in Amphisorus hemprichii Hikami et al 2011) and M. rossii (Reymond et al 2013).…”
Section: Discussionmentioning
confidence: 40%
“…Similar results were also found by Vogel & Uthicke [23], who also observed either no effect or enhanced growth in M. vertebralis after 45 days exposure to as high as 1925 ppm CO 2 . Conversely, a decline in shell weight of newly asexually produced specimens of Amphisorus hemiprichii was detected by Hikami et al [52] after four weeks exposed to low pH/ high pCO 2 conditions. Both species live on and are adapted to the shallow areas of the reef [34].…”
Section: Discussionmentioning
confidence: 99%
“…and tropical reef-associated taxa, including amphisteginids, calcarinids, and nummulitids, that host algal endosymbionts (e.g., Lee, 2006). Responses to elevated pCO 2 among the rotaliids have varied from reduced calcification, especially in taxa that lack algal symbionts (e.g., Allison et al, 2010;Dissard et al, 2010;Haynert et al, 2011), to enhancement of growth and photosynthesis in those with algal symbionts, at least at intermediate pCO 2 levels (e.g., Fujita et al, 2011;Hikami et al, 2011). Among the porcelaneous Miliolida, most experiments have utilized members of the Family Soritidae that host dinoflagellate symbionts.…”
Section: Introductionmentioning
confidence: 98%